Last night [large type] - Rice, Luanne (Center Point Large Print, 2024)
"A fierce blizzard is burying the eastern seaboard, but on the icy Rhode Island shore renowned artist Maddie Morrison finds warm sanctuary from a contentious divorce at the legendary Ocean House. Hours later, her body is found buried under a blanket of snow and her little daughter, CeCe, has disappeared without a trace. For Detective Conor Reid; his brother, Tom, a coast guard commander; and Maddie's grieving sister, Hadley, the posh hotel becomes ground zero for an investigation. Trapped by the blizzard, they must hunker down and determine who in the young mother's life could have possibly wanted her dead. There are stories of a twisted romantic past. Of old jealousies and resentments that still cut to the bone. And a history of greed, rage, and revenge that created the perfect storm for murder. A storm that has just begun."--